Analysis of Generation and Attraction in Bogor Regency (Case Study: Tenjolaya Sub-District, Tamansari Sub-District and Tenjolaya Sub-District) - Zakiyah, Qonita; Murtejo, Tedy; Chayati, Nurul (Universitas Ibn Khaldun Bogor, 2023)
Tenjolaya Subdistrict, Tamansari Subdistrict, and Ciomas Subdistrict of Bogor District has an area of 61.74 km2, divided into 25 villages, and 1 urban-village with those total populations density are 4,819.7 people/km2. The increasing population and significant development in the region has increased the movement of traffic flows to and from the region, which is expected to cause some particular problems in traffic congestion on Road segments. This research aims to make the model of the trip generation and the trip attraction caused by land use such as education area, medical, office, lodging, physical fitness center and tourism in the three sub-districts. MKJI 2017 is used as a data processing guideline for the method of calculation of transport analysis. Then use Trip Generation Manual and modelled into SATURN software. Total trip generations from 3 sub-districts of the study area are 4,403.78 trips/hour, and with total trip attractions are 6,165.33 SMP/hour. The design of the transportation modelling equation for Ciomas subdistrict, Tamansari District, and Tenjolaya subdistrict is 21,230 – 0,950 (X). The Model of trip generation and trip attraction has a value of R2 = 0,9687. The level of service is obtained index in the range of A until D, with an average is B, indicating a relatively stable condition. although in some areas, it is still necessary to repair and improve road network infrastructure, and strive for a comfortable and efficient alternative public transport system (time, cost, energy) to transfer people from private vehicles to Public transport.